Epidemiological, bacteriological profile and bacterial resistance of urinary tract infections at pregnant woman in prenatal consultation in African setting - Koffi, Koffi Abdoul; Aka, Edèle Kacou; Apollinaire, Horo; Britoh, Alice Mlan; Konan, Jean Marie Perel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Urinary tract infection is a common pathology during pregnancy due to hormonal and morphological changes. Objective of this study was to improve management of urinary tract infection during prenatal care. Methods: A total of 987 pregnant women who have been in prenatal care have freely accepted to participate in cross-sectional study carried out from 1st May 2016 to 30th April 2017 at Yopougon University Hospital (Abidjan Côte d’Ivoire) were included. Patients were submitted to questionnaire by one of investigators for epidemiological component and then physical examination was carried out by her attending physician for clinical component. Then at laboratory urine was taken for culture after dipstick test. Results: Of the 987 patients included 9.4% had a urinary tract infection of which 81.7% were asymptomatic. Significant risk factors retained were existence of a history of urinary tract infection (OR=0.46; p=0,038) and gestational age of pregnancy (OR=0.44; p=0.05). Urine culture isolated germs were mainly Escherichia Coli (51.6%) and Klebsiella pneumoniaie (23.6%). These germs were all susceptible to cephalosporins. They had resistances of more than 50% to penicillins. Conclusions: Escherichia coli and Klebsiella pneumoniae are most common germs of urinary tract infections in pregnant women. Escherichia coli is not susceptible to penicillins with a resistance of 70% for penicillins except for clavulanic acid amoxicillin. It appears as first choice antibiotic for our prescriptions in case of probabilistic antibiotic therapy.